¿Estuvo el orden del comercio internacional de la posguerra dirigido al éxito mientras que el orden monetario de Bretton Woods establecido en 1944 estaba signado por el fracaso? - de Urioste, Ricardo (Pontificia Universidad Católica del Perú, 2023)
This paper explores the reasons embedded in the original architecture of both the international trade and monetary regimes that determined different outcomes for both. It proposes that the original version of the Bretton Woods monetary regime showed faster its essential failures and basically had to be replaced as early as 1971, while the trade regime embodied in the GATT and later in the WTO managed to at least survive until present day. It posits that correspondence (or the lack of it) of the basic characteristics of the said regimes with the underlying political reality where the regimes would apply (in line with Ruggie´s depiction of «embedded liberalism») accounts for the differentiated outcomes. It explains that the international trade regime showed more flexible traits that allowed it to adjust to the underlying political and led to its survival. The lack of that adaptability element would likewise explain the early demise of the original Bretton woods scheme.

Este trabajo explora las razones incorporadas en la arquitectura original de los regímenes internacionales de comercio y monetario que determinaron los distintos desenlaces para ambos. Propone que la versión original del régimen monetario de Bretton Woods mostró más rápidamente sus fallas esenciales y tuvo que ser remplazado tempranamente en 1971, mientras que el régimen internacional de comercio logró al menos sobrevivir hasta ahora. Postula que el alineamiento (o la ausencia de este) de las características básicas de dichos regímenes con la realidad política subyacente sobre la cual deberían aplicarse esos regímenes (en la línea de la descripción de Ruggie del concepto de embedded liberalism) explica la diferenciación en los resultados. Explica que el régimen internacional de comercio reveló caracteres de mayor flexibilidad que le permitieron ajustarse a la realidad política subyacente lo que llevó a su sobrevivencia. La falta de ese elemento de adaptabilidad explicaría igualmente el temprano deceso del esquema original de Bretton Woods.
Was the post-war international trade order bound to succeed while the Bretton Woods monetary order established in 1944 was doomed to fail?
Keywords: International trade regime; International monetary regime; GATT; WTO; IMF; Bretton Woods; Embedded liberalism; Foreign trade policy; International monetary policy; Institutional flexibility; Régimen del comercio internacional; Régimen monetario internacional; GATT; OMC; FMI; Bretton Woods; Embedded liberalism; Política de comercio internacional; Política monetaria internacional; Flexibilidad institucional; https://purl.org/pe-repo/ocde/ford#5.09.01